Nutritional management of pediatric nephrotic syndrome regarding oxidative stress and antioxidant balance - Jechel, Elena; Nedelcu, Alin Horatiu; Dragan, Felicia; Lupu, Vasile Valeriu; Starcea, Iuliana Magdalena; Mocanu, Adriana; Rosu, Solange Tamara; Streanga, Violeta; Russu, Ruxandra; Baciu, Ginel; Danielescu, Ciprian; Salaru, Delia Lidia; et al. (Frontiers in Immunology, 2025)
Pediatric nephrotic syndrome remains a complex clinical entity, with incompletely elucidated pathogenetic mechanisms, in which oxidative stress appears to have a substantial etiopathogenic role. Recent evidence supports the involvement of redox imbalance in podocyte damage, impaired glomerular function, and systemic decline. All this suggests that antioxidant interventions can favorably modulate the course of the disease. This narrative review aims to synthesize the most relevant data from the current literature on the interaction between oxidative stress and nephrotic syndrome in children, with a focus on the therapeutic potential of antioxidants. The analysis focuses on the molecular mechanisms by which oxidative stress contributes to the progression of renal dysfunction, the role of oxidative biomarkers in disease monitoring, and the ability of antioxidants to reduce the need for immunosuppressants and corticosteroids, thus contributing to the decrease in associated morbidity. The translational perspectives of antioxidant therapy are also discussed, in the context of the urgent need for effective adjuvant strategies with a safety profile superior to conventional therapies. By integrating these data, the paper supports the valorization of antioxidant interventions as an emerging direction in the management of pediatric nephrotic syndrome and substantiates the need for controlled clinical trials, with rigorous design, in this field.